Avaliação do impacto da pequena açudagem na vazão regularizada de um reservatório estratégico. Estudo de caso: Açude Araras - CE - Almeida, José Herbert Medeiros (2016)
The SMAP model is a model of hydrologic simulation and, when properly calibrated its parameters, this generates a series of inflows for a given basin; this study in particular, to the basin of Araras weir located in Acaraú basin. For calibration of the model were used as extracted rainfall historical input data series of the National Water Agency website, evapotranspiration data obtained by FAO and a historical series of fluviometria the Cajazeiras Desk obtained from the FUNCEME. The SMAPM version is responsible for generating a time series of the reservoir inflow disregarding the impact of small açudagem while SMAPRPA version is responsible for generating a number of inflows to the reservoir computing the impact of small açudagem. This work studied the simulation of these hydrological models - SMAPM and SMAPRPA - and the corresponding inflows obtained were made water balance simulations in the tank, one for each version, in order to compare the stored volume generated from simulations of flow with the actual volume accumulated in the dam Araras based on the 1986 monitoring of operational data to 2014 assigned by COGERH. The model generated SMAPRPA more satisfactory results both from a visual inspection as in Pearson correlation resulting in r of 88.27% to 80.21% SMAPRPA against SMAPM for indicating that the small açudagem consequently brought a decrease in the regulated flow as confirmed by graphs 32 and 33. the decrease in the regulated flow is due to the fact that since 1960 there has been a great encouragement from the federal and state government to spread the small açudagem in an attempt to democratize access to water, and according to simulations made, there was a "loss" of water depth equivalent to 17mm of rain resulting in nearly 60 hm³ - 6.73% of the capacity of Araras - ceasing to flow into the weir Araras damaging future projections allocation and impacting the theoretical flow Q90 of 6.14 m³ / s, in addition to causing the feeling that in dry years the drought has been more intense than recorded by the responsible agency as these 60 hm³ be lost by evaporation without contributing anything to regularize flows as small açudagem has intranual character and not regularized.